2017
DOI: 10.17116/jnevro201711710211-19
|View full text |Cite
|
Sign up to set email alerts
|

Gut human microbiota and multiple sclerosis

Abstract: Recently the relationship between gut microbiota changes and the development of immune-mediated diseases of the central nervous system (CNS) has been reported. This review presents literature data on the effect of gut microbiota on the function of the immune and nervous systems. The authors discuss possible mechanisms of the relationship between gut microbiota changes and CNS diseases on the model of multiple sclerosis (MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 86 publications
0
4
0
1
Order By: Relevance
“…Interestingly, this reduction was evident for patients with active MS, whereas patients in remission exhibited comparable diversity levels to the healthy population. Further studies verified this association of disease activity status with alterations of the relative abundance of microbes in the gut, with Firmicutes and Bacteroidetes exhibiting higher relative abundances reviewed by Kozhieva et al [61]. These studies indicated the following: Though it is widely accepted that the gut microbiome in patients with MS is characterized by moderate dysbiosis, a clear and consistent multiple sclerosis microbiome phenotype has not been described.…”
Section: Mechanisms Of Immune-modulation By Intestinal Microbiota-climentioning
confidence: 94%
“…Interestingly, this reduction was evident for patients with active MS, whereas patients in remission exhibited comparable diversity levels to the healthy population. Further studies verified this association of disease activity status with alterations of the relative abundance of microbes in the gut, with Firmicutes and Bacteroidetes exhibiting higher relative abundances reviewed by Kozhieva et al [61]. These studies indicated the following: Though it is widely accepted that the gut microbiome in patients with MS is characterized by moderate dysbiosis, a clear and consistent multiple sclerosis microbiome phenotype has not been described.…”
Section: Mechanisms Of Immune-modulation By Intestinal Microbiota-climentioning
confidence: 94%
“…41,51 Moreover, insufficient exercise, obesity, gut microbiota disorders, and an "inflammatory diet" (high in meat and fat, and low in fiber and ratio of omega-3/ omega-6 fatty acids) are also known to be incentives of chronic inflammation. [52][53][54] Chronic inflammation has been linked to many chronic diseases either directly or indirectly, such as atherosclerosis, myocardial infarction, chronic heart failure, Parkinson's disease, Alzheimer's disease, asthma, diabetes, psoriasis, osteoporosis, and cancer. [55][56][57] Almost 20% of human cancers and infections have been related to chronic inflammation.…”
Section: The Initiation and Resolution Of Inflammationmentioning
confidence: 99%
“…The involvement of dopamine in depression, cognitive impairments, and fatigue in MS was shown [ 11 , 12 , 13 , 14 ]. In addition, dopamine has been shown to modulate the gut–brain axis, which plays an important role in the development of autoimmunity, psychiatric disorders, and neuroinflammation [ 15 , 16 , 17 ]. It is important to note that depression is one of the most common symptoms in MS and may aggravate its course, which could be explained by similar pathogenetic mechanisms of MS and depression, including an enhanced Th17 immune response [ 18 , 19 ].…”
Section: The Involvement Of Dopamine In the Development Of Clinical Symptoms In Msmentioning
confidence: 99%